(untitled) (The International Journal of Educational Sciences and Arts, 2023)
This study aims to measure the effect of applying enrichment activities on developing self-care skills among children in kindergarten. The sample of the study included (40) male and female kindergarten children in a public-school kindergarten. The study tools included: a measure of some self-care skills illustrated for a kindergarten child, and a program based on enrichment activities to develop some self-care skills for a child of this school stage. The researcher also used the experimental approach with two experimental and control groups, and the results concluded that the enrichment activities were effective in developing some self-care skills for kindergarten children.